The Effect of Rapid Automatic Naming on Reading Readiness for Children with Reading Difficulties in Elementary School - Salma Nadiyah; Sunardi Tukimin; Budi Susetyo; Iding Tarsidi; Ranti Novianti; Fadly Halim Hutasuhut; Atma Widia (INCLUSIVE EDUCATION, 2022)
In addition to phonological deficit, children who have difficulty in reading can also have RAN (rapid automatic naming) deficit or both. RAN is a strong predictor of the cause of reading difficulties and is a characteristic of reading disability or dyslexia. This study aims to know the impact of the rapid automatic naming intervention on dyslexic students in elementary schools. The research uses a quantitative approach to the Single Subject Research (SSR) method of A-B-A design. We tested the effect of teaching rapid automatic naming on the ability to quickly name objects, color digits, and letters in 4 subjects who had almost the same reading difficulties at the same grade level. The results showed that the teaching of rapid automatic naming affected increasing children's speed in naming objects, colors, digits, and letters. The significant effect of the rapid automatic naming teaching intervention shows that understanding the principles of rapid automatic naming is beneficial for students with dyslexia. The four experimental subjects showed an increase in the speed of naming objects, colors, digits, and letters after the intervention.